2014
DOI: 10.1007/s10971-014-3287-7
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical performance and in vivo bioactivity of functionally graded PEEK–HA biocomposite materials

Abstract: A functionally graded material (FGM) of polyetheretherketone (PEEK)-hydroxyapatite (HA) with a symmetrical three-layer structure containing 8.7, 2.6 and 8.7 vol% HA, respectively, is successfully fabricated by hot pressing and evaluated by scanning electron microscopy and tensile testing. A good bonding between the HA particles and the PEEK matrix is achieved by virtue of an in situ method in fabricating each PEEK-HA composite layer. There are no apparent microcracks and microscopic interfaces within each laye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…In addition, medical grade PEEK tends to degrade when it is held in excess of 30 minutes at temperatures above 400℃ in the absence of a vacuum. Ma et al [41] used compression moulding to make a simple functionally graded PEEK/HA composites. Roeder's group at University of Notre Dame, USA, reported successful use of compression moulding and particulate leaching to make porous bioactive PEEK/HA-whisker composite [5][6][7][8] .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, medical grade PEEK tends to degrade when it is held in excess of 30 minutes at temperatures above 400℃ in the absence of a vacuum. Ma et al [41] used compression moulding to make a simple functionally graded PEEK/HA composites. Roeder's group at University of Notre Dame, USA, reported successful use of compression moulding and particulate leaching to make porous bioactive PEEK/HA-whisker composite [5][6][7][8] .…”
Section: Discussionmentioning
confidence: 99%
“…Hydroxyapatite is brittle (Ma et al, 2014a), and it always destroy PEEK's excellent mechanical properties after blending with PEEK. To enhance the mechanical properties of composite materials, Ma J. et al (2020) used a 3D braiding, self-retention, hot pressing method to prepare an N-HA and PEEK blending material.…”
Section: Peek/ha Compositesmentioning
confidence: 99%
“…Initially, composites were prepared by addition of HA during PEEK synthesis which gives excellent dispersion of HA in PEEK matrix. Three layers of different HA vol% were stacked in a steel die before hot pressing to create functionally graded PEEK/ HA composites [195]. It can be concluded that even with different ways of manufacturing of composite scaffolds, the in vitro and in vivo results show increment in bioactivity with HA inclusion.…”
Section: Peek Powdermentioning
confidence: 99%